Helicobacter pylori Infection Is Associated with an Increased Risk of Hyperemesis Gravidarum: A Meta-Analysis - Lin Li; Lingling Li; Xiaoying Zhou; Shuping Xiao; Huiyuan Gu; Guoxin Zhang (Gastroenterology Research and Practice)
Background. Several studies have shown a possible involvement of Helicobacter pylori (H. pylori) infection in individuals with hyperemesis gravidarum (HG), but the relationship remains controversial. This meta-analysis was performed to validate and strengthen the association between HG and H. pylori infection. Methods. PubMed, Embase, and Web of Science databases up to March 20, 2014, were searched to select studies on the prevalence of H. pylori infection between pregnant women with HG and the normal pregnant control subjects. Results. Of the HG cases, 1289 (69.6%) were H. pylori-positive; however, 1045 (46.2%) were H. pylori-positive in control group. Compared to the non-HG normal pregnant controls, infection rate of H. pylori was significantly higher in pregnant women with HG (OR = 3.34, 95% CI: 2.32–4.81, P<0.001). Subgroup analysis indicated that H. pylori infection was a risk factor of HG in Asia, Africa, and Oceania, especially in Africa (OR = 12.38, 95% CI: 7.12–21.54, P<0.001). Conclusions. H. pylori should be considered one of the risk factors of HG, especially in the developing countries. H. pylori eradication could be considered to relieve the symptoms of HG in some intractable cases.